2013
DOI: 10.1111/j.1468-2362.2013.12033.x
|View full text |Cite
|
Sign up to set email alerts
|

Pure or Wake‐up‐Call Contagion? Another Look at the EMU Sovereign Debt Crisis

Abstract: We test whether the sharp increase in sovereign spreads of euro-area countries with respect to Germany after the explosion of the Greek crisis was due to deteriorating macroeconomic and fiscal fundamentals or to some form of financial contagion. Our analysis includes indicators of domestic and external imbalances which were mostly disregarded by previous studies, and distinguishes between investors' increased attention to the variables which ultimately determine the creditworthiness of a sovereign borrower (wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 59 publications
5
117
1
Order By: Relevance
“…In this case, markets revisited the perception of private credit and banking sector issues in the pricing of sovereign risk after the onset of the sovereign crisis in Ireland and later in other countries. In this respect, our results are also in line with Giordano et al (2013) who analyzed the Eurozone sovereign bond markets and found evidence for contagion based on the wake-up call of the Greek crisis.…”
Section: Economic Impact and Wake-up Call Hypothesissupporting
confidence: 91%
“…In this case, markets revisited the perception of private credit and banking sector issues in the pricing of sovereign risk after the onset of the sovereign crisis in Ireland and later in other countries. In this respect, our results are also in line with Giordano et al (2013) who analyzed the Eurozone sovereign bond markets and found evidence for contagion based on the wake-up call of the Greek crisis.…”
Section: Economic Impact and Wake-up Call Hypothesissupporting
confidence: 91%
“…Complementary to fiscal, macroeconomic and financial market variables several studies distinguish between the period before and after the sovereign debt crisis to account for a structural change in the relationship between government bond yields and its determinants (Bernoth et al, 2012;Giordano et al, 2013;Beirne and Fratzscher, 2013;De Haan et al, 2014). The sovereign debt crisis started at the end of 2009, when it became clear that fiscal policy in Greece was not sustainable.…”
Section: A Fundamental Drivers Of Government Bond Yieldsmentioning
confidence: 99%
“…This variable reflects changes in global risk aversion (see e.g. Giordano et al, 2013;Beirne and Fratzscher, 2013;Aizenman et al, 2013;D'Agostino and Ehrmann, 2013;De Haan et al, 2014). A positive sign is expected since in more volatile markets the default risk of countries may increase which results in higher spreads and nominal yields.…”
Section: A Datamentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) concluded that most of the level of sovereign risk and the rise during the crisis period usually can be explained by a country's own economic fundamentals and its underlying fundamental contagion, while regional contagion explains a much more modest magnitude of sovereign risk. Based on studies by Giordano M. et al (2013), andFavero (2013), the increased unexplainable part of bond spread dynamics since 2010 could be related to the appearance of a new systemic risk, i.e., the risk of a euro break-up, that is, the risk that one or more countries might exit from the EMU.…”
Section: Related Literature Reviewmentioning
confidence: 99%